Description of Lead Levels in the Hair Online Motorbike Drivers Based on Years of Service - Utami, Arlinda Karisma Putri; Harningsih, Tri (Indonesian Journal of Global Health Research, 2023)
Air pollution by motor vehicle exhaust emissions can release lead into the air. Online motorbike drivers are people at risk of being exposed to lead metal. Exposure to lead metal can accumulate in hair and cause toxic effects. The purpose of this study was to determine the level of lead in online motorbike drivers based on years of service.This type of research is descriptive project. Primary data is data obtained from the results of measuring lead levels in the hair of online motorbike drivers. The population of this research is online motorbike drivers in Solo area. Sampling technique used in this research was quota sampling, where 10 samples of online motorbike drivers were taken who met the researchers' criteria. Data was analyzed descriptively to determine lead levels in the hair of online motorbike drivers. The results of questionaires and direct interviews is taken. All samples identification of lead level using by Atomic Absorption Spectrophotometer. The results for each of the 10 respondents were SP01 (0,7817 ug/gr), SP02 (2,0917 ug/gr), SP03 (0,6045 ug/gr), SP04 (0,6210 ug/gr), SP05 (0,3191 ug/gr), SP06 (2,4239 ug/gr), SP07 (1,1067 ug/gr), SP08 (4,5903 ug/gr), SP09 (0,8983 ug/gr), SP10 (0,4668 ug/gr). Based on research conducted at the Yogyakarta Health and Calibration Laboratory. It can be concluded that lead levels of online motorbike drivers do not exceed the threshold set by the Ministry of Health, (<10 µg/gr). This study found the lowest level at SP 05 (0,3191 ug/gr) with a working period of 1 year and the highest level was at SP 08 (4,5903 ug/gr) with a working period of 5 years as an Online motorbike drivers.